(untitled) (Clinics, 2021)
OBJECTIVES: Coronary artery disease is the primary cause of death and is responsible for a high number of hospitalizations worldwide. Ventricular remodeling is associated with worse prognosis following ST-segment elevation myocardial infarction (STEMI) and is a risk factor for ventricular dysfunction and heart failure. This study aimed to identify the predictors of ventricular remodeling following STEMI. Additionally, we evaluated the clinical, laboratory, and echocardiographic characteristics of patients with anterior wall STEMI who underwent primary percutaneous intervention in the acute phase and at 6 months after the infarction. METHODS: This prospective, observational, and longitudinal study included 50 patients with anterior wall STEMI who were admitted to the coronary care unit (CCU) of a tertiary hospital in Brazil between July 2017 and August 2018. During the CCU stay, patients were evaluated daily and underwent echocardiogram within the first three days following STEMI. After six months, the patients underwent clinical evaluation and echocardiogram according to the local protocol. RESULTS: Differences were noted between those who developed ventricular remodeling and those who did not in the mean±standard deviation levels of creatine phosphokinase MB isoenzyme (CKMB) peak (no remodeling group: 323.7±228.2 U/L; remodeling group: 522.4±201.6 U/L; p=0.008) and the median and interquartile range of E/E’ ratio (no remodeling group: 9.20 [8.50–11.25] and remodeling group: 12.60 [10.74–14.40]; p=0.004). This difference was also observed in multivariate logistic regression. CONCLUSIONS: Diastolic dysfunction and CKMB peak in the acute phase of STEMI can be predictors of ventricular remodeling following STEMI.